Corruption in Northeast Brazil: A qualitative approach for socio-economic development - Rocha de Sousa, Miguel (2015)
This study starts from a literature review on corruption, departing from its ancient roots, going to its modern prevalence and perception. We focus our approach on the NE Brazil region. The main contribution is that it is the first qualitative approach which assesses corruption specifically in the NE Brazil. We use 21 interviews to political actors: senators and deputies, collected along one and half year in Brasilia, the capital of Brazil, in 2012-13, as in one of us (Carneiro’s Phd, 2013). A causal link is established between corruption and under-development, namely at its socioeconomic roots. We believe this study is path-breaking, because as it focus on one of the most depressed regions in Brazil, can serve as toolkit for socio-economic development policies in Latin America. The innovative approach comes from the fact of using qualitative text analysis to measure the impact of corruption on the (official) discourse on development. A tentative conclusion, with some recommendations for alike situations is attempted by abridging the different socio-economic and political dimensions. We also use Sen’s, Furtado’s, Rose-Ackerman’s among a few concepts to cross the notions of corruption in NE’s discourse with their theoretical framework, by the use of the software WebQDA. JEL codes: K42; 017; Z13